Utility of different positron emission tomography/computed tomography tracers in the evaluation of incidentally detected dual malignancies: An experience from a tertiary care center - Kumar, Ram; Gupta, Nitin; Verma, Ritu; Belho, Ethel (World Journal of Nuclear Medicine, 2021)
Multiple primary malignancies in a cancer patient are not a rare occurrence. The most common presentation of multiple primary malignancies is dual malignancies. The usefulness of different positron emission tomography (PET)/computed tomography (CT) tracers in the evaluation of dual synchronous primary malignancies is not well documented. Here, we present a case series, where two patients, referred for PET/CT, after being diagnosed with one primary malignancy were found to be having a second primary malignancy, diagnosed incidentally in PET/CT, further validated by PET/CT with another tracer.
Keywords: Dual malignancies; fluorodeoxyglucose positron emission tomography/computed tomography; positron emission tomography/computed tomography tracers; prostate-specific membrane antigen positron emission tomography/computed tomography